Inflation targeting or fiscal activism? - Roberto M. Billi (Sveriges Riksbank, 2022)
I study the welfare performance of a policy regime of fiscal activism in which fiscal policy acts as an automatic stabilizer and controls inflation, while monetary policy pegs the nominal interest rate. When evaluated through the lens of a standard New Keynesian model, accounting for price and wage rigidities and for a zero lower bound (ZLB) on the nominal interest rate, fiscal activism can substantially outperform inflation targeting in the face of both demand shocks and technology shocks. Fiscal activism can also eliminate the occurrence of ZLB episodes.
Keywords: E24; E31; E52; E63; 330; automatic stabilizers; fiscal and monetary interactions; government debt